2022
DOI: 10.2298/tsci22s1191s
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent flows around rectangular and triangular turbulators in baffled channels a computational analysis

Abstract: The present paper highlights a computational analysis of air-flows around rectangular and triangular turbulators inside baffled heat exchanger channels in order to improve heat transfer between the fluid and their heated areas. The dynamic and thermal fields as well as fluid temperature curves at the outlet of the exchanger are studied. The computational study is conducted by utilizing SIMPLE algorithm with FLUENT system based on the finite volumes. The analysis clearly demonstrated the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The model established by Mohammed Amine Amraoui et al [12] concerns a numerical study on a plane air solar collector equipped with square obstacles where they gave the diagram of the model after having made the mesh of this model which allowed them to find results on the temperature distribution, the speed and the turbulence field and finally they presented graphs on the average Nusselt number, the average friction coefficient versus the Reynolds number. The study, which aims to improve the efficiency of the solar collector by introducing two fluid flow paths, was carried out by Mohammed Amine Amraoui et al [13], who compared their results with those reported in the existing literature. These results will contribute to the development of advanced solar collector designs and promote sustainable use of solar energy.…”
Section: Introductionmentioning
confidence: 99%
“…The model established by Mohammed Amine Amraoui et al [12] concerns a numerical study on a plane air solar collector equipped with square obstacles where they gave the diagram of the model after having made the mesh of this model which allowed them to find results on the temperature distribution, the speed and the turbulence field and finally they presented graphs on the average Nusselt number, the average friction coefficient versus the Reynolds number. The study, which aims to improve the efficiency of the solar collector by introducing two fluid flow paths, was carried out by Mohammed Amine Amraoui et al [13], who compared their results with those reported in the existing literature. These results will contribute to the development of advanced solar collector designs and promote sustainable use of solar energy.…”
Section: Introductionmentioning
confidence: 99%